Syringe fading as treatment for feeding refusal. Issue 4 (8th October 2014) - Groff, Rebecca A.; Piazza, Cathleen C.; Volkert, Valerie M.; Jostad, Candice M.
Abstract The efficacy of nonremoval of the cup or spoon as treatment for feeding refusal is dependent on prevention of escape from presentations. In the current investigation, 1 child with feeding refusal escaped presentations during nonremoval of the cup and spoon by clenching his teeth. Therefore, we used a syringe to deposit liquids and solids, increased the volume of liquids and solids in the syringe, and conducted syringe‐to‐cup and syringe‐to‐spoon fading.